Pre-verbal infants perceive emotional facial expressions categorically. Issue 3 (3rd April 2019) - Cong, Yong-Qi; Junge, Caroline; Aktar, Evin; Raijmakers, Maartje; Franklin, Anna; Sauter, Disa
ABSTRACT: Adults perceive emotional expressions categorically, with discrimination being faster and more accurate between expressions from different emotion categories (i.e. blends with two different predominant emotions) than between two stimuli from the same category (i.e. blends with the same predominant emotion). The current study sought to test whether facial expressions of happiness and fear are perceived categorically by pre-verbal infants, using a new stimulus set that was shown to yield categorical perception in adult observers (Experiments 1 and 2). These stimuli were then used with 7-month-old infants ( N   =  34) using a habituation and visual preference paradigm (Experiment 3). Infants were first habituated to an expression of one emotion, then presented with the same expression paired with a novel expression either from the same emotion category or from a different emotion category. After habituation to fear, infants displayed a novelty preference for pairs of between-category expressions, but not within-category ones, showing categorical perception. However, infants showed no novelty preference when they were habituated to happiness. Our findings provide evidence for categorical perception of emotional expressions in pre-verbal infants, while the asymmetrical effect challenges the notion of a bias towards negative information in this age group.